Potential of alarmin-targeted bispecific and combination therapies in airway disease - Komori, H. Kiyomi; Ortega, Hector (Frontiers in Allergy, 2025)
Thymic stromal lymphopoietin (TSLP), IL-33, and IL-25 are epithelial-derived proinflammatory alarmin cytokines that drive inflammatory airway diseases such as asthma and chronic obstructive pulmonary disease (COPD). Targeted inhibition of these proteins has demonstrated varying degrees of efficacy in patients with asthma and COPD. As the biology of inflammatory respiratory disease is complex, combination approaches that directly inhibit multiple targets may provide deeper efficacy in a broader patient population. Here, we review the biology of alarmins and the development landscape for monotherapies and multispecific alarmin inhibitors.